2020
DOI: 10.3390/molecules25133020
|View full text |Cite
|
Sign up to set email alerts
|

Degradative Ability of Mushrooms Cultivated on Corn Silage Digestate

Abstract: The current management practice of digestate from biogas plants involves its use for land application as a fertilizer. Nevertheless, the inadequate handling of digestate may cause environmental risks due to losses of ammonia, methane and nitrous oxide. Therefore, the key goals of digestate management are to maximize its value by developing new digestate products, reducing its dependency on soil application and the consequent air pollution. The high nitrogen and lignin content in solid digestate make it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 61 publications
(74 reference statements)
4
9
0
Order By: Relevance
“…Several previous works have shown that different species of Pleurotus are able to grow on various agro-residues, including grape pomace [2], hazelnut shells [23], banana leaves, sunflower stalk, cotton stalk, and sugar cane straw, proving their potentiality [10]. The mycelial growth of different fungi on digestate, including Pleurotus spp., has already been demonstrated in previous works [24,25]. Nevertheless, there is a general lack of research on the industrial application of this promising cultivation substrate.…”
Section: Introductionmentioning
confidence: 81%
“…Several previous works have shown that different species of Pleurotus are able to grow on various agro-residues, including grape pomace [2], hazelnut shells [23], banana leaves, sunflower stalk, cotton stalk, and sugar cane straw, proving their potentiality [10]. The mycelial growth of different fungi on digestate, including Pleurotus spp., has already been demonstrated in previous works [24,25]. Nevertheless, there is a general lack of research on the industrial application of this promising cultivation substrate.…”
Section: Introductionmentioning
confidence: 81%
“…Comparatively, P. eryngii (Km = 0.2; BE = 39.6 kg dt −1 ) converted more substrate into biomass, indicating that this species was the most effective exotic mushroom for biotransformation, followed by F. velutipes (Km = 0.15; BE = 30.4 kg dt −1 ) and A. aegerita (Km = 0.05; BE = 31.8 kg dt −1 ), based on biodegradability. A study by Fornito et al [33] on the degradative ability of mushrooms on silage consisting of corn reported incomplete colonization of the substrate by A. aegerita. The mycelial network of the exotic fungus was not capable of completely colonizing the substrate; thus, the bioconversion of labile C (an unstable fraction of the total C pool in raw materials) into biomass decreased, as did the biological efficiency, which is consistent with the lowest biodegradability of A. aegerita in this study.…”
Section: Biodegradability and Biological Efficiencymentioning
confidence: 99%
“…The substrates from in vitro test were analyzed after 30 days of mycelial growth, as previously described by Fornito et al, 2020 [44]. Parts of dried fruiting bodies (cap, hymenophore, and stipe) grown on the HS and WS-BC of each species were placed on the diamond crystal, and pressure was applied with a compression clamp.…”
Section: Micro Atr-ftir Spectroscopy Analysismentioning
confidence: 99%
“…In an earlier study, it was also used to show how physical harm had an effect on tissue structure and the aging process [43]. The most intriguing application of this technique is currently the degradation processes of various agricultural waste for mushroom cultivation [44,45].…”
Section: Introductionmentioning
confidence: 99%